Contextura da música-imagem: diálogos com o filme Barry Lyndon - Filipe Jhonata Schettini Azevedo (2022)
The relationship between music and image in cinema is not just an example of the dynamics intermedia inherent to this art form. This is a human creation in the arts that makes it possible a huge range of impacts and meanings, created and polished in a content audio-visual. In this dissertation, a concept term was elaborated to serve as a film analysis tool for possible deep interactions between art-media music and image-media art in cinema: image-music. This approach highlighted possible intermedia, technological, semiological and philosophical interactions in this intertwining, demonstrating that this union generates a result that goes beyond magnitude as the sum of the parts. For that, The film Barry Lyndon (1975), by Stanley Kubrick, was used as a guiding example, for be a reference work for the music-image relationship. To observe this relationship between the music and image, Deleuze-Gattarian concepts were used, in interaction with the studies of Cinema, Semiology, Intermediality, Music in cinema and other areas, to observe this relationship between the music and image. If it is through this kind of art that we can also express ourselves and communicate, it is in this kind of deep machination art that we found the way to confront our reality with our time.